Knowledge and Attitudes of General Population's Toward Rheumatoid Arthritis in Hail, Saudi Arabia - Alshurtan, Kareemah; Aldugieman, Mnieaam Zaal; Bader Jazzaa Alshammari; Ali Turki Alodily; Yateem, Hisham Ali; Alanzi, Kholood Hussein; Almallahi, Anwar Essa; Alahmadi, Raed Hassan; Almijrad, Salem Abdulaziz (South Eastern European Journal of Public Health, 2024)
Background: A chronic inflammatory autoimmune illness, rheumatoid arthritis (RA) mainly affects small, symmetrical joints, especially those in the hand, wrist, and foot. However, it can also affect other joints and systems. Joint deformity, persistent pain, and a reduced quality of life are brought on by recurrent assaults. Aim: The objective of the research is to evaluate the general public's awareness and insights regarding rheumatoid arthritis in Hail, Saudi Arabia. Method: The cross-sectional research took place on people in Hail who were at least 18 years old and over. A self-administered questionnaire was distributed among Hail population using online platforms primarily social media. The questionnaire includes basic demographic characteristics, types of RA, the causes of RA, the symptoms, the risk factors, complications, treatment of RA and whether they know what RA is or not. Results: 532 people in responded to the questionnaire; of them, 42.5% were female and 50.9% were male. 8.3% had received a diagnosis of RA, and 60.0% correctly associated it with joint pain and morning stiffness. 67.3% believed that RA is not a contagious disease. A significant majority (56.6%) correctly identified that women are more likely to develop RA. Regarding risk factors, 28.0% acknowledged smoking as a significant factor. A notable finding is that 63.7% were uncertain about RA's impact on pregnancy. Knowledge about specific joint involvement varied, with 60.0% correctly associating RA with inflammation in small joints. Conclusion: The results indicate that while some participants demonstrated a correct comprehension of the disease, there were misconceptions, particularly regarding the joint pain characteristic, types of joint involvement and extra-articular manifestations. These results emphasize how crucial it is to set educational initiatives in place to clear up these misunderstandings and raise community understanding about rheumatoid arthritis.